Adaption of active boundary conditions in structural fire testing. (9th December 2019) - Qureshi, Ramla Karim; Elhami-Khorasani, Negar; Gernay, Thomas
Abstract : Purpose: This paper aims to investigate the need for active boundary conditions during fire testing of structural elements, review existing studies on hybrid fire testing (HFT), a technique that would ensure updating of boundary conditions during a fire test, and propose a compensation scheme to mitigate instabilities in the hybrid testing procedure. Design/methodology/approach: The paper focuses on structural steel columns and starts with a detailed literature review of steel column fire tests in the past few decades with varying axial and rotational end restraints. The review is followed with new results from comparative numerical analyses of structural steel columns with various end constraints. HFT is then discussed as a potential solution to be adapted for fire testing of structural elements. Challenges in contemporary HFT procedures are discussed, and application of stiffness updating approaches is demonstrated. Findings: The reviewed studies indicate that axial and rotational restraints at the boundaries considerably influence the fire response of steel columns. Equivalent static spring technique for simulating effect of surrounding frame on an isolated column behavior does not depict accurate buckling and post-buckling response. Additionally, numerical models that simulate fire performance of a column situated in a full-frame do follow the trends observed in actual test results up until failure occurs, but these simulations do not necessarily capture post-failure performance accurately. HFT can be used to capture proper boundary conditions during testing of isolated elements, as well as correct failure modes. However, existing studies showed cases with instabilities during HFT. This paper demonstrates that a different stiffness updates calculated from the force-displacement response history of test specimen at elevated temperature can be used to resolve stability issues. Originality/value: The paper has two contributions: it suggests that the provision of active boundary conditions is needed in structural fire testing, as equivalent static spring does not necessarily capture the effect of surrounding frame on an isolated element during a fire test, and it shows that force-displacement response history of test specimen during HFT can be used in the form of a stiffness update to ensure test stability.